Vertically Segregated Structure and Properties of Small Molecule–Polymer Blend Semiconductors for Organic Thin‐Film Transistors. (27th August 2012) - Shin, Nayool; Kang, Jihoon; Richter, Lee J.; Prabhu, Vivek M.; Kline, R. Joseph; Fischer, Daniel A.; DeLongchamp, Dean M.; Toney, Michael F.; Satija, Sushil K.; Gundlach, David J.; Purushothaman, Balaji; Anthony, John E.; et al.
Abstract A comprehensive structure and performance study of thin blend films of the small‐molecule semiconductor, 2, 8‐difluoro‐5, 11‐bis(triethylsilylethynyl)anthradithiophene (diF‐TESADT), with various insulating binder polymers in organic thin‐film transistors is reported. The vertically segregated composition profile and nanostructure in the blend films are characterized by a combination of complementary experimental methods including grazing incidence X‐ray diffraction, neutron reflectivity, variable angle spectroscopic ellipsometry, and near edge X‐ray absorption fine structure spectroscopy. Three polymer binders are considered: atactic poly(α‐methylstyrene), atactic poly(methylmethacrylate), and syndiotactic polystyrene. The choice of polymer can strongly affect the vertical composition profile and the extent of crystalline order in blend films due to the competing effects of confinement entropy, interaction energy with substrate surfaces, and solidification kinetics. The variations in the vertically segregated composition profile and crystalline order in thin blend films explain the significant impacts of binder polymer choice on the charge carrier mobility of these films in the solution‐processed bottom‐gate/bottom‐contact thin‐film transistors.